Increasing Students' Interest and Learning Outcomes with the Make a Match Learning Model in Junior High School Physics Science Learning - Wibowowati, Lilis (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2022)
Science education can build knowledge, add insight, think creatively, and critically. Science also contains abstract concepts, so that students’ interest and learning outcomes in science learning are not optimal. Teachers have not varied in using learning models, causing students to feel bored and less active in participating in learning. This study aims to increase the students’ interest and learning outcomes in the substance pressure and its application in everyday life using the Make a Match learning model. A total 34 students of VIII grade participate in this study. The research method uses a classroom action research design which consists of two cycles, namely cycle I and cycle II. Each cycle consists of four stages, namely 1) planning, 2) implementation, 3) observation, and 4) reflection. The research subjects were students of class VIII H of SMP Negeri 2 Majenang. Data collection techniques using cognitive tests, observation, documentation, and field notes. Quantitative data were analyzed using quantitative data analysis techniques and qualitative data were analyzed using qualitative data analysis techniques. The results of the first cycle research showed that 68% of students' interest in learning meant that they had not reached the success criteria, 71% of students' learning outcomes had not reached the KKM and 29% of the subjects had reached the KKM, which meant that they had not reached the success criteria. Cycle II shows that 75% of the students' interest in learning means that they have reached the success criteria, 78% of the students' learning outcomes have reached the KKM, which means they have reached the success criteria. The conclusion of the study shows that the application of the Make a Match learning model can increase the interest and learning outcomes of students in learning science on substance stress and its application in everyday life for class VIII SMP.